NIMS fatigue data sheet on low- and high-cycle fatigue properties of boron steel - Yoshiyuki Furuya; Hideaki Nishikawa; Hisashi Hirukawa (Science and Technology of Advanced Materials: Methods)
The new fatigue data sheet, No. 134, discloses the low- and high-cycle fatigue properties of boron steel. The low-cycle fatigue tests under strain-controlled conditions used incremental step tests to show cyclic stress-strain curves and constant-strain amplitude tests to identify fatigue lives. The incremental step tests reveal that cyclic softening occurs in boron steel; the cyclic yield stress is comparable to that of other steels. The constant-strain amplitude tests revealed three types of fatigue life curves relative to total strain amplitude, plastic strain amplitude and elastic strain amplitude. The crossing points between the plastic strain amplitude curve and the elastic strain amplitude curve were at around 103 or 104 cycles. The high-cycle fatigue tests comprised uniaxial loading fatigue testing and rotating bending fatigue testing. The high-cycle fatigue strength revealed slight differences between heats that were related to differences in tensile strength. On the other hand, there were only minor differences between the uniaxial loading fatigue test results and the rotating bending fatigue test results. The fatigue strength of the boron steel samples was equivalent to that of low-alloy steel, rather than to that of carbon steel. This resulted from the excellent hardenability of the boron steel samples and indicated high fatigue performance. In the high-cycle fatigue tests, several specimens fractured at over 107 cycles without evidence of internal fracturing, so the fatigue limits were not clear. The long-life surface fracturing might be attributable to very mild corrosion effects by air.